Developmental Language Disorder as a Multidimensional Neurodevelopmental Spectrum: Implications for Diagnosis. - McGregor, Karla K.; Goffman, Lisa; Plante, Elena; Werfel, Krystal (Journal of Speech, Language & Hearing Research, 2025)
Purpose: We aimed to create a comprehensive understanding of the dilemmas involved in the diagnosis of developmental language disorder (DLD) and to highlight the potential of a multidimensional spectral account of DLD for addressing these dilemmas. Method: We conducted an integrative literature review. Conclusions: Considerable gains in understanding the genetics and neurobiology of DLD provide new explanations for long-observed phenomena such as heterogeneity of presentation, phenotypic overlap with other neurodevelopmental conditions, and the challenges of diagnosis. Although categorical nosologies benefit diagnostic decision making, facilitate communication, and align well with bureaucratic systems, they offer overly simple ways of defining DLD. The presentation of DLD is broad rather than narrow, spectral rather than categorical, and dynamic rather than static; therefore, DLD is better described as a multidimensional spectral system than as a categorical entity. It is not practical or even advisable to abandon the traditional categorical framing of DLD at this point. However, maintaining awareness of the tension between the categorical framing and the spectral nature of DLD may improve diagnosis, prognosis, and alignment with the construct of neurodiversity.